Teenage Births in Maine: Positive Trends But More to Be Done - King, Leslie; Marks, Stephen (Maine Policy Review, 2002)
Teen birth rates in Maine have fallen by 34 percent over the past decade, the fourth highest decline in the nation. However, as King and Marks point out, a low birthrate of 29.8 percent in 1999 still exceeds the teenage birthrate in most other industrialized countries in the world by a substantial margin. Moreover, when the authors compared Maine’s predominantly white population with non-Hispanic whites in other states, Maine’s success is not as remarkable. Indeed, the teenage birthrate of Maine’s non-Hispanic white population is higher than every other state in the Northeast corridor with the exception of Delaware. All of this suggests that more needs to be done in Maine. The authors review the tremendous progress made through school- and community-based family planning programs in Maine. They call for more education, more funding for the Family Planning Association of Maine, and more economic/social supports for young adults most in need.